Visible-light-induced cyclization of cyclic N-sulfonyl ketimines to N-sulfonamide fused imidazolidines. Issue 18 (21st April 2022) - Wang, Xiaotong; Shi, Anzai; Huang, Xian-Qiang; Chen, Xiaolan; Li, Tiesheng; Qu, Lingbo; Yu, Bing
Abstract : An eosin Y-catalyzed annulation reaction of cyclic N -sulfonyl ketimines and N -arylglycines was reported to construct N -sulfonamide-fused imidazolidines under visible-light induced metal-free conditions. Abstract : A visible-light-induced metal-free cascade cyclization of cyclic N -sulfonyl ketimines with N -arylglycines for the construction of N -sulfonamide-fused imidazolidines was developed. The procedure employed 3 mol% of eosin Y as the photocatalyst at room temperature under visible light irradiation, providing various N -sulfonamide-fused imidazolidines in good yields (32 examples, up to 86% yields).